Hubungan kecemasan matematika dan kemampuan verbal dengan keterampilan numerasi peserta didik kelas V sekolah dasar - Aisyah Nurul 'Aini; Supianto Supianto (Didaktika Dwija Indria, 2025)
This study aims to investigate the relationship between mathematics anxiety, verbal ability, and numeracy skills among fifth-grade elementary school students. Specifically, it examines: (1) the correlation between mathematics anxiety and numeracy skills; (2) the correlation between verbal ability and numeracy skills; and (3) the joint correlation of mathematics anxiety and verbal ability with numeracy skills. The research employed a correlational survey method. The population consisted of fifth-grade students from public elementary schools in Cluster III of the Banjarsari District, comprising approximately 53 schools. A total of 83 students from three schools were selected using a cluster random sampling technique. Data collection instruments included a mathematics anxiety questionnaire and multiple-choice tests for verbal ability and numeracy skills. The results of the analysis show that: (1) there is a significant correlation between mathematics anxiety and numeracy skills (ry1 =  -0,431; tcount = 4.295 > ttable = 1.990); (2) there is a significant correlation between verbal ability and numeracy skills (ry2 = 0,423; tcount = 4,196 > ttable = 1.990); and (3) there is a significant simultaneous correlation between mathematics anxiety and verbal ability with numeracy skills (ry12 = 0,531 ; Fcount = 15,692 > Ftable 3,111). These findings highlight the importance of both emotional and cognitive factors in shaping students' numeracy proficiency.